Advancing Community Building for ASEAN - Michael S.H. Heng (2018)
© 2015, Springer Science+Business Media Dordrecht. This is a policy paper supporting the vision of ASEAN leaders in the project of ASEAN Community building. However, it goes beyond their declarations to argue for a more thorough going adoption of the norms of the United Nations and to promote more people-to-people activities and ASEAN consciousness among the people. ASEAN was established in 1967 with the aim to strengthen regional cooperation to deal with the geopolitical challenges of the Cold War. It has scored successes in the realm of economy. Driven by the dynamics of globalization, ASEAN has aspired to become a full-fledged community of nations. It aims to widen its scope to include social and cultural dimensions, social justice, and human rights. The most progressive manifestation of this is the ASEAN Charter. To advance the project of the ASEAN Community, this paper makes suggestions at two levels, namely the level of ideas and the level of activities, with some reflections on nation building. A nation at peace with itself based on social justice and human rights contributes to regional community building. If and when it does come about, the ASEAN Community will represent a new ASEAN identity, with a new moral and political order, and it will be able to articulate global issues in international forums with moral authority and moral coherence.